Disrupted IRF6-NME1/2 Complexes as a Cause of Cleft Lip/Palate. (October 2017) - Parada-Sanchez, M.T.; Chu, E.Y.; Cox, L.L.; Undurty, S.S.; Standley, J.M.; Murray, J.C.; Cox, T.C.
Mutations and common polymorphisms in interferon regulatory factor 6 ( IRF6 ) are associated with both syndromic and nonsyndromic forms of cleft lip/palate (CLP). To date, much of the focus on this transcription factor has been on identifying its direct targets and the gene regulatory network in which it operates. Notably, however, IRF6 is found predominantly in the cytoplasm, with its import into the nucleus tightly regulated like other members of the IRF family. To provide further insight into the role of IRF6 in the pathogenesis of CLP, we sought to identify direct IRF6 protein interactors using a combination of yeast 2-hybrid screens and co-immunoprecipitation assays. Using this approach, we identified NME1 and NME2, well-known regulators of Rho-type GTPases, E-cadherin endocytosis, and epithelial junctional remodeling, as bona fide IRF6 partner proteins. The NME proteins co-localize with IRF6 in the cytoplasm of primary palatal epithelial cells in vivo, and their interaction with IRF6 is significantly enhanced by phosphorylation of key serine residues in the IRF6 C-terminus. Furthermore, CLP associated IRF6 missense mutations disrupt the ability of IRF6 to bind the NME proteins and result in elevated activation of Rac1 and RhoA, compared to wild-type IRF6, when ectopically expressed in 293T epithelial cells. Significantly, we also report the identification of 2 unique missense mutations in the NME proteins in patients with CLP (NME1 R18Q in an IRF6 and GRHL3 mutation-negative patient with van der Woude syndrome and NME2 G71V in a patient with nonsyndromic CLP). Both variants disrupted the ability of the respective proteins to interact with IRF6. The data presented suggest an important role for cytoplasmic IRF6 in regulating the availability or localization of the NME1/2 complex and thus the dynamic behavior of epithelia during lip/palate development.